Predictors of Acute Heart Failure Decompensation at 30 days After Discharge. Results from a Multidisciplinary Heart Failure unit. (14th October 2021) - Gorriz Magana, J; Abad Romero, R; Nieto Ibanez, D; Olsen Rodriguez, R; Perela Alvarez, C; Espinosa Pascual, M J; Fraile Sanz, A; Perea Egido, J; Alonso Martin, J
Abstract: Background: Unexpected readmissions are frequent among heart failure (HF) patients (pts). These are associated with high economic cost and have great clinical relevance. HF Units are cornerstones to build early intervention to prevent readmissions. Due to their natural history HF implies multiple readmissions, with high costs and clinical relevance. HF Units are cornerstones to avoid early readmission. Purpose: We aimed to identify predictors of early HF decompensation (at 30 days) that could recognize high risk patients during the systematic follow-up in our Multidisciplinary Heart Failure Program (MHFP) that was launched in February 2019. Methods: We carried out an analytical and observational study including all patients admitted to our University Hospital, which covers 220, 000 individuals. We built a predictive multivariate model with Logistic Regression using relevant predictors (clinical and statistical) that were identified. Results: A total of 235 acute HF decompensations were referred to our MHFP. The 69.8% of them were men with median age of 75 years (interquartile range, IR 71–81). Mean left ventricular ejection fraction was 41% (IR 29–54%. A total of 55% with reduced and 30% with preserved ejection fraction). The 26% of the patients had right ventricle dilatation and 35% disfunction. Left bundle branch block was present in 27% of them. Median glomerular filter was 54ml/min (IR 37–73ml/min) and median pulmonary artery systolic pressure 50mmhg (IR 42–66mmg). Mean time to readmission was 19.6 months. Among decompensations that we detected in MHFP during 30 days after discharge, just 39% (5 pts) could be detected and managed in day hospital and 61% (8 pts) as an admission. In Table 01 we show the predictors that were included in the multivariate model. We finally found that it was just the NTproBNP level in a blood test within 7–10 days after discharge (R 2 N 0.59) which remains significative. Risk increased 1.20 times (1.000185 1000 ) for each 1000 units rise in blood test (Table 1. Graph 1). Conclusion: According to our results, detecting high NTproBNP levels in blood test within 7–10 days after discharge might predict a higher HF decompensation risk. The final multivariate model would explain 59% of those events at one month after discharge. Funding Acknowledgement: Type of funding sources: None.